1980
DOI: 10.1113/jphysiol.1980.sp013441
|View full text |Cite
|
Sign up to set email alerts
|

Projections from Pacinian corpuscles and rapidly adapting mechanoreceptors of glabrous skin to the cat's spinal cord.

Abstract: SUMMARY1. Single axons innervating Pacinian corpuscles and rapidly adapting mechanoreceptors of the foot and toe pads were injected with horseradish peroxidase near their entrance to the lumbosacral spinal cord in cats anaesthetized with chloralose and paralysed with gallamine triethiodide. Subsequent histochemistry revealed the morphology of the intra-spinal parts of the axons.2. All Pacinian corpuscle axons that could be traced into the dorsal root bifurcated upon entering the cord into ascending and descend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 32 publications
(42 reference statements)
1
37
0
Order By: Relevance
“…The distribution of synaptic boutons to as many as four laminae (III-VI) is similar to the distribution of collaterals from axons of Pacinian corpuscles (Brown et al 1980a), but Pacinian corpuscle collaterals form continuous sagittal columns of terminal arborizations in laminae III and IV.…”
Section: Sa Type II Cutaneous Axon Collaterals Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The distribution of synaptic boutons to as many as four laminae (III-VI) is similar to the distribution of collaterals from axons of Pacinian corpuscles (Brown et al 1980a), but Pacinian corpuscle collaterals form continuous sagittal columns of terminal arborizations in laminae III and IV.…”
Section: Sa Type II Cutaneous Axon Collaterals Discussionmentioning
confidence: 82%
“…Subsequent histochemistry provided detailed information about the anatomy of the collaterals entering the dorsal horn. The results demonstrate that Type II slowly adapting units have collaterals in the spinal cord quite different from those of any other cutaneous or muscle afferent unit so far studied (Brown, Rose & Snow, 1977, 1978Brown & Fyffe, 1978, 1979Brown, Fyffe & Noble, 1980a;Fyffe, 1979;Light & Perl, 1979).…”
Section: Introductionmentioning
confidence: 88%
“…In the same context, an examination of the terminal arbors of small myelinated AS high threshold mechanoreceptive primary axons in lamina I following intra-axonal injections of HRP (Light and Perl, 1979) revealed no branches resembling ultrafine primary axons. In addition, the extensive analyses of the laminar distribution of the many different kinds of small myelinated primary axons which arborize in the dorsal horn (Brown et al, 1977(Brown et al, , 1980Light and Perl, 1979) has shown that only the AS high threshold mechanoreceptive primary axon generates endings in lamina I (Light and Perl, 1979). Physiological studies have described small myelinated cold thermoreceptive and heat nociceptive primary axons which terminate in the dorsal horn (see Price and Dubner, 1977 for review).…”
Section: Discussionmentioning
confidence: 99%
“…Scale bars, 0.5 pm. generates most of its endings in lamina III (Light and Perl, 1979), the field receptor afferent which generates many endings in laminae III and IV (Light and Perl, 1979), the slowly adapting type I afferents which generate most of their endings in lamina IV, the guard hair afferents with their flame-shaped arbors which ramify across lamina III and IV (Brown et al, 1977), the Pacinian corpuscle afferents which generate endings across laminae III to VI (Brown et al, 1980), the rapidly adapting afferents of glabrous skin with endings in laminae III (Brown et al, 1980), and the large Ia muscle afferents which generate their endings in the ventral horn (Brown and Fyffe, 1978;Burke et al, 1979). Each of these myelinated primary axons shares several features in common with the large caliber primary axons described in lamina I in this study: they each give rise to several, thin, branched, ending-bearing collaterals which are finer than their thicker parent branches; these ending-bearing branches, in turn, generate several relatively widely spaced large bulbous endings, The large caliber primary axons of lamina I described in this report closely match the morphological characteristics of the terminal arbors of the AS high threshold mechanoreceptors in lamina I (Light and Perl, 1979) in terms of the morphology of their endings and their ending-bearing collaterals as well as in the frequent reversal of directions of their thicker parent branches.…”
Section: Discussionmentioning
confidence: 99%
“…E. R. MEYERS AND P. J. SNOW thin myelinated or unmyelinated afferent fibres which enter the cord over the dorsal roots (Brown, Rose & Snow, 1977bBrown, Fyffe & Noble, 1980;Brown, Fyffe, Rose & Snow, 1981;Light & Perl, 1979a, b;De Groat, Nadelhaft, Morgan & Shauble, 1978). Also, available evidence suggests that primary afferents entering the cord through the ventral roots do not give rise to terminals below the nucleus proprius (Light & Metz, 1978).…”
Section: Axonal Projectionsmentioning
confidence: 99%